Rheology of phonolitic magmas - the case of the Erebus lava lake - Le Losq, Charles; Neuville, Daniel R.; Moretti, Roberto; Kyle, Philip R.; Oppenheimer, Clive (Earth and Planetary Science Letters, 2015)
International audience Long-lived active lava lakes are comparatively rare and are typically associated with low-viscosity basaltic magmas. Erebus volcano, Antarctica, is unique today in hosting a phonolitic lava lake. Phonolitic magmas can erupt explosively, as in the 79 CE Plinian eruption of Vesuvius volcano, Italy, and it is therefore important to understand their physical properties. The phonolite at Erebus has slightly higher silica content than that at Vesuvius yet its present activity is predominantly non-explosive. As a contribution to understanding such contrasting eruptive behaviour, we focus on the rheological differences between these comparable magmas. In particular, we evaluate the viscosity of the Erebus phonolite magma by integrating new experimental data within a theoretical and empirical framework. The resulting model enables estimation of the Erebus melt viscosity as a function of temperature, crystal and water concentrations, with an uncertainty of, at most, ± 0.45 log (Pa s). Using reported ranges for these parameters, we predict that the magma viscosity in the upper region of the plumbing system of Erebus ranges between 10 5 and 10 7 Pas. This is substantially higher than has been hitherto considered with significant implications for modelling the dynamics of the lava lake, conduit and magma reservoir system. Our analysis highlights the generic challenges encountered in calculation of magma viscosity and presents an approach that can be applied to other cases.